Harmonizing Interfaith Differences in Pakistan Under Islamic Directions (Khairulummah, 2022)
Interfaith harmony requires both the promotion of good change and the cultivation of compassion and peace among followers of many religions. People from various religious origins communicate with one another both institutionally and interpersonally, which promotes a more positive outlook on politics and other national and international contacts in various nations. A compulsory code of behavior that a person, a group of people, and society as a whole should abide by in all things of the world is the cornerstone of the humanistic idea of virtue known as conformism. Because people are flawed and make mistakes, harmony helps people to grow and build themselves to the point where they are superior, teachable, and faultless. Peace and harmony can only be maintained in society if the rights of followers of all religions, including life, property, and the pursuit of happiness, are protected. This study's purpose is to explain how Islamic teachings in Pakistan might reconcile interfaith differences. The data was collected using both quantitative and qualitative methods. The University of Gujrat, Ghazi University, DG Khan, Swabi Women University, and Shaheed Benazir Bhutto Women University, Peshawar are among the four universities where the 220 questionnaires are distributed. Through the use of graphs and tables in the excel software, the students' opinions have been examined. As well as we approached different libraries to collect material i.e., Hameed Ullah, IIUI, Islamabad, Alama Iqbal Open University, SBBWUP, and Archive library Peshawar. As a result of our research, we have concluded that Pakistan is an Islamic country that fully protects minorities in all aspects of life. This includes the freedom to practice their religion following their beliefs, to visit places of worship without hindrance, to access educational opportunities, and to seek employment anywhere. Non-Muslims are reportedly to be treated better in Pakistan.